Percepções discentes sobre a Estratégia de Saúde da Família e a escolha pela especialidade de Medicina de Família e Comunidade - Issa, Afonso Henrique Teixeira Magalhaes (2014)
Objective: To analyze the perceptions of undergraduates in medicine in relation to the work of the Family Health Strategy (FHS) and the influencing factors in choosing the specialty of Family Medicine and Community (FM). Materials and Methods: An exploratory and qualitative study of a cross-sectional nature involving undergraduates in the 11th period of the medical school of the University Center of Anápolis (UniEVANGÉLICA) which is located in the Central-West region of Brazil. The study involved the examination of data collected from the body of students involved in a course of study who have been selected after approval by the Ethics and Research Committee. In the research, two instruments for collecting data and information were used: Firstly a questionnaire and secondly a roadmap for semi-structured interviews. This approach was taken in order to Identify Socioeconomic Characterization along with the Identification of Occupational Aspirations and analysis of factors that influence their choice of FM by using the technique of content analysis. Results and Discussion: None of the interviewed graduates opted to specialize in FM. The low social status, low wages, lack of labor rights, the experience of little contact with medical specialists during the course, the poor solutions in FHS, with poor working conditions and limited opportunity for professional growth showed up as negative influences in their choice. FM have previously examined the social relevance, comprehensive clinical work, bond with patients, as well as greater contact with medical experts in FM for new graduates to present themselves as positive influences on the perception of choices. Final Thoughts: The most effective actions that can ensure the recovery of the FHS as a more inclusive and positive workplace and one that offers a more recognized appreciation of family medicine as a medical specialty is as outlined. Better wages and greater social recognition of the work of the FM are factors that should be considered in policy actions. A further major factor would be ensuring labor rights and conditions for personal accomplishment in the FHS expert in FM. The inclusion of experts in FM graduation may assist in identifying students with this specialty. Further studies should be conducted to broaden the understanding of the subject and deeper questioning of this important theme for consolidation of the Unified Health System (SUS).